STRATEGI PENERAPAN NATIONAL SINGLE WINDOW DI PELABUHAN TANJUNG EMAS SEMARANG (SUATU KONSEP DARI STUDI KASUS DI PELABUHAN TANJUNG EMAS SEMARANG) - Harun Al Rasyid Martohandoyo; Budhi Hascaryo Iskandar; John Haluan; Fedi A. Sondita; Hasjimdo Djalal (Buletin PSP, 2008)
This is a continuation from previous paper with the title of The Authority of some State-Institutions in Tanjung Emas Port, Semarang Central Java. This paper discusses about the staregy to implement Indonesian National Single Window (NSW) concept in Indonesia especialy in Tanjung Emas Port, Semarang. The SWOT and AHP were used in the data analysis. The result shows that there are five strategies to implement NSW in Indonesia especialy in Tanjung Emas Port, Semarang.